The causal role of smoking on the risk of hip or knee replacement due to primary osteoarthritis: a Mendelian randomisation analysis of the HUNT study. Issue 6 (June 2017) - Johnsen, M.B.; Vie, G.Å.; Winsvold, B.S.; Bjørngaard, J.H.; Åsvold, B.O.; Gabrielsen, M.E.; Pedersen, L.M.; Hellevik, A.I.; Langhammer, A.; Furnes, O.; Flugsrud, G.B.; Skorpen, F.; et al.
Summary: Objective: Smoking has been associated with a reduced risk of hip and knee osteoarthritis (OA) and subsequent joint replacement. The aim of the present study was to assess whether the observed association is likely to be causal. Method: 55, 745 participants of a population-based cohort were genotyped for the rs1051730 C > T single-nucleotide polymorphism (SNP), a proxy for smoking quantity among smokers. A Mendelian randomization analysis was performed using rs1051730 as an instrument to evaluate the causal role of smoking on the risk of hip or knee replacement (combined as total joint replacement (TJR)). Association between rs1051730 T alleles and TJR was estimated by hazard ratios (HRs) and 95% confidence intervals (CIs). All analyses were adjusted for age and sex. Results: Smoking quantity (no. of cigarettes) was inversely associated with TJR (HR 0.97, 95% CI 0.97–0.98). In the Mendelian randomization analysis, rs1051730 T alleles were associated with reduced risk of TJR among current smokers (HR 0.84, 95% CI 0.76–0.98, per T allele), however we found no evidence of association among former (HR 0.97, 95% CI 0.88–1.07) and never smokers (HR 0.97, 95% CI 0.89–1.06). Neither adjusting for body mass index (BMI), cardiovascular disease (CVD) nor accounting for the competing risk of mortality substantially changed the results. Conclusion: This study suggests that smoking may be causally associated with the reduced risk of TJR. Our findings add support to the inverse association found in previous observational studies. More research is needed to further elucidate the underlying mechanisms of this causal association.